Analisis Implementasi Akad Musyarakah Dalam Pembiayaan Modal Usaha Pada Perbankan Syariah Di Indonesia - Elen Sri Ega Putri; Mohd Winario; Diany Mairiza (EL-EMIR Institute, 2025)
Mudharabah is one of the fundamental forms of business partnership contracts in Islamic economic jurisprudence, established between the capital provider (shahibul maal) and the entrepreneur or business manager (mudharib). In the context of modern Islamic banking, the mudharabah contract serves as a crucial instrument for both collecting and distributing customers' funds, while also representing the values of justice, transparency, and partnership in economic activity. The implementation of mudharabah in contemporary Islamic financial institutions often faces various challenges that warrant critical examination from the normative perspective of Islamic law. This study aims to thoroughly examine how the mudharabah contract is applied in modern Islamic banking practices and to evaluate its compliance with the principles of fiqh muamalah as established by both classical and contemporary Islamic scholars. The approach used in this study is descriptive-analytical, by exploring primary sources of Islamic law (the Qur’an and Hadith), secondary sources (including ijma’, qiyas, and fatwas issued by the National Sharia Council—DSN-MUI), as well as operational practices adopted by Islamic banking institutions in Indonesia and several other Muslim-majority countries. In practice, the mudharabah contract has undergone significant modifications to align with the demands of the modern and complex banking sistem.